Some properties of Jordan-Ehlers spacetime - G. Mohanty; U. K. Panigrahi (International Journal of Mathematics and Mathematical Sciences)
It is shown that for cylindrically symmetric Jordan-Ehlers spacetime, either the charged scalar meson field associated with meson rest mass M or the charged perfect fluid cannot be the source for generating gravitation.